1981
DOI: 10.1002/bem.2250020112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short electromagnetic pulses on brain acetylcholine content and spontaneous motor activity of mice

Abstract: Mice were exposed to a single 15-ms or 25-ms pulse of 2,450-MHz microwaves which increased brain temperature by 2 degrees C or 4 degrees C, respectively. Immediately after exposure, the mice became hypokinetic but began recovering within 5 minutes. The 25-ms pulse (18.7 j deposited in the brain) caused a significant decrease in acetylcholine content of the whole brain, probably owing to increased permeability of the membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…A few studies have been added to the classical literature on thermal tolerance. Modak et al [1981] showed that the motor activity of mice would decrease immediately after exposure to single, intense pulses of 2450 MHz RF energy and remain at a low level for at least 5 min thereafter. A 25 ms pulse at an energy dose of 18.7 J was more effective than a 15 ms pulse at 14.25 J, and body temperature was elevated more at the longer (þ4 8C) than at the shorter (þ2 8C) duration.…”
Section: Thermal Tolerance and Lethalitymentioning
confidence: 99%
“…A few studies have been added to the classical literature on thermal tolerance. Modak et al [1981] showed that the motor activity of mice would decrease immediately after exposure to single, intense pulses of 2450 MHz RF energy and remain at a low level for at least 5 min thereafter. A 25 ms pulse at an energy dose of 18.7 J was more effective than a 15 ms pulse at 14.25 J, and body temperature was elevated more at the longer (þ4 8C) than at the shorter (þ2 8C) duration.…”
Section: Thermal Tolerance and Lethalitymentioning
confidence: 99%
“…Previously, it has been demonstrated that exposure to radiofrequencies induced changes in different cholinergic parameters such as acetylcholine concentration (Modak et al 1981) and release (Testylier et al 2002), choline uptake (Lai et al 1987;Lai et al 1989) and acetylcholinesterase activity (Dutta et al 1992;Ahmed et al 2006;Valbonesi et al 2016). Such alteration of neurotransmitter system may influence behavior.…”
Section: Discussionmentioning
confidence: 98%
“…Various expenments have shown effects of microwaves on cholinergic functions. A decrease in brain concentration of acetylcholine has been reported in mice exposed to pulsed microwaves, which increased the body temperature by 2 4 C (Modak et al, 1981). Acute microwave irradiation has been reported to inhibit membrane-bound acetylcholinesterase activity in the vagal heart preparation (Young, 1980) and also in the guinea pig brain (Baranski, 1972).…”
Section: Discussionmentioning
confidence: 99%